Personal Protective Equipment Compliance In Preventing Hearing Loss In Agro-Industrial Area - Musta’adah, Iftitatul; Nasywa, Adinda; Efendi, Anggit Drajad; Kurniyawan, Enggal Hadi; Kurniawan, Dicky Endrian; Afandi, Alfid Tri; Nur, Kholid Rosyidi Muhammad (International Journal of Midwifery and Health Sciences, 2024)
Background: In Indonesia the impact of noise that causes hearing loss is still high compared to other countries in Southeast Asia. Noise can cause hearing loss in workers if the scale of the noise is high and occurs continuously. It can also trigger a decline in health that will have an impact on the performance of workers. Objective: to Analysis of PPE Compliance in Preventing Hearing Loss in Agro-Industrial Area. Methods: The research in this study used the literature review method. This search strategy uses several databases such as Pubmed, ResearchGate, and Google Scholar. This search use keywords PPE, Hearing Loss, and Agro-industrial. Results: Increasing noise intensity, duration of work, and duration of exposure can cause hearing loss because the inner hair cells and supporting cells are damaged. The longer the working period, the greater the noise exposure it will receive. The use of PPE can effectively prevent noise-induced hearing loss. Conclusion: Workers exposed to noise are highly susceptible to hearing loss. It depends on the intensity of the noise, the duration of exposure, the sensitivity of the individual or the worker itself and the frequency of the noise. Noise can be prevented, one of which is by using personal protective equipment when working. In this case, nurses can educate related to the use of PPE to prevent hearing loss.